Temporary employment as an atypical form of employment – comments in relation to the applicable legal regulation (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
One of the atypical forms of work performance dynamically developing on the Polish labour market is temporary employment, under which a temporary employment agency as an employer (employing entity) engages employees or non-employees in order to direct them to perform temporary work for the user employer. According to the latest data compiled by the Polish HR Forum, the number of temporary employees increased from 433,000 in 2010 to 648,000 in 2021, and the estimated value of the entire Polish temporary labour market is now over PLN 3 billion. The aim of the study is to introduce the reader to the issue of temporary employment, which was the subject of the III National Scientific Conference from the series „Atypical employment relations” organized in Łódź by the Centre for Atypical Employment Relations of the Faculty of Law and Administration of the University of Lodz on December 3, 2020. The author will present his own reflections on the Act on the Employment of Temporary Workers after its amendment, which entered into force on 1 June 2017.